A study on ship capsizing due to collision - Ibn Awal, Zobair; Islam, M. Rafiqul (Faculty of Mechanical Engineering, 2008)
This paper investigates the ship capsizing due to collision with another ship in calm water. A mathematical model on collision dynamics has been developed and validated. The dynamic characteristic (roll in particular) has been studied numerically. Searches have been made to find the survivability boundaries in terms of striking velocity, coefficient of restitution, collision angle, collision time and vertical position of hitting point. Maximum amplitude of rolling motion has been determined against the said parameters and have been presented as 3D surface charts which enable to identify safe boundaries of operation for two given variables at a time. This particular approach of collision simulation has the potential of analysing operational risks during a ship’s design stage and thereby incorporates necessary modifications if required. Recommendations have been put forward for future studies.